Formulasi dan Evaluasi Sediaan Obat Kumur Dari Ekstrak Fermentasi Bawang Lanang (Allium sativum L.) - Marbun, Eva Diansari; Sapitri, Alfi; Arisetya, Dian; Thaib, Cut Masyithah; Haliza, Aipak; Purba, Elizabet Kristina; Helmi, Helmi (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Mouthwash is a dilute concentration of antibacterial solution used to fight oral microbes, fight oral infections, cleansers, to eliminate bad breath, fresh and antiseptic. Mouthwash plays an important role in an individual's oral hygiene, mouthwash helps to relieve symptoms of gingivitis, inflamed gums and can also be relied on to destroy pathogenic bacteria. (Banu & Gayathri, 2016). The purpose of this study was to see if the extract from fermented Bawang Lanang (Allium sativum L) can be formulated into a mouthwash. This research method is an experimental laboratory. By including preparation of materials, sample identification, Making fermented Bawang Lanang, making extracts, extract yields, phytochemical screening, then formulated into a mouthwash. After that, an evaluation of the physical preparation of the mouthwash was carried out (organoleptic test, pH test, viscosity test and stability test). The results of the evaluation of the mouthwash preparation starting from the organoleptic test, pH test did not exceed pH 7, viscosity test of the series was stable for 3 months. Conclusion: Mouthwash preparations containing fermented ethanol extract of male shallots can be used as mouthwash, with good stability.